2014
DOI: 10.1371/journal.pone.0104844
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Magnetic Resonance Imaging of Scar Development Following Pulmonary Vein Isolation: A Prospective Study

Abstract: AimsCardiovascular magnetic resonance (MR) provides non-invasive assessment of early (24-hour) edema and injury following pulmonary vein isolation (by ablation) and subsequent scar formation. We hypothesize that 24-hours after ablation, cardiovascular MR would demonstrate a pattern of edema and injury due to ablation and the severity would correlate with subsequent scar.MethodsFifteen atrial fibrillation patients underwent cardiovascular MR prior to pulmonary vein isolation, 24-hours post (N = 11) and 30-days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Inflammation or edema could also occur in the thin wall of the left atrium (LA) or right ventricle (RV). For example, radio-frequency ablation for treatment of atrial fibrillation causes LA edema, which can be detected with T 2 weighted imaging (4446); however T 2 weighted imaging in LA or RV is challenging and interpretation is subjective. Conventional bright blood T 2 maps do not allow accurate measurement of LA T 2 due to partial voluming.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation or edema could also occur in the thin wall of the left atrium (LA) or right ventricle (RV). For example, radio-frequency ablation for treatment of atrial fibrillation causes LA edema, which can be detected with T 2 weighted imaging (4446); however T 2 weighted imaging in LA or RV is challenging and interpretation is subjective. Conventional bright blood T 2 maps do not allow accurate measurement of LA T 2 due to partial voluming.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that myocardial edema can occur within 1 day after radiofrequency ablation. [1][2][3][4][5][6][7] The degree of edema depends on the intensity and quantity of radiofrequency energy during pulmonary vein ablation. [8] The fluid is usually absorbed in about 1 to 3 months, [3,9,10] and the speed of resorption is closely related to early recurrence of AF, [11] which may be due to changes in conductance and transmembrane ion currents soon after ablation or to cardiomyocyte edema.…”
Section: Postoperative Myocardial Edemamentioning
confidence: 99%
“…CMR LGE could have a significant role also during the postablation phase. LA wall thickening and oedema following pulmonary vein ablation correlate with a 30-day LGE scar [ 81 ]. Atrial regions ablated show a higher contrast uptake and thinner myocardium, compared with regions with pre-existing LGE.…”
Section: La Size and Function To Assess Stroke Risk And Before Ablati...mentioning
confidence: 99%